Clinical characteristics in 113 Turkish vitiligo patients - Arýcan, Özer (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2008)
Background and designd: This study assesses clinical findings and coexisting dermatological and systemic diseases of Turkish vitiligo patients. Materials and methods: One hundred and thirteen patients were included in the study overa 2-year period. Patients were diagnosed by clinical findings and Wood's lamp. Each patient's age, sex, date of onset, first localization, clinical type, disease activity, coexisting systemic or dermatological diseases, and familial history were recorded. A complete blood count, routine biochemistry tests, serum vitamin B12 and folic acid, thyroid hormones, and complete urinalysis were done. All patients were examined by the outpatient psychiatricservice. Results: The majority of patients were female (n = 60, 53.1%), and the rest males (n = 53, 46.9%). Their ages ranged from 2 to 76 years. Eighty-seven patients showed a progression of vitiligo. The age at onset of the condition varied from 6 months to 75 years. In 58 patients vitiligo was generalized, whereas in 47 it was localized. The most common siteof onset was the upper limbs (38.1%), followed by the head and neck (24.8%), trunk (15%), lower limbs (13.3%), and genital area (8.8%). Leukotrichia was present in 21 patients; only 12 had a family history of vitiligo. The most common psychiatric diagnoses were depression (32.7%) and anxiety (15.9%). Coexisting cutaneous and systemic disorders were present in 22 patients. Conclusions: The disease predominantly affects the younger population.
Keywords: Comorbidity; Diagnosis; kožne bolezni; Soobolevnost; Turčija; Turkey; Vitiligo